Brazilian society of rheumatology methodological guide for the development of evidence-based clinical guidelines in rheumatology - Ana Karla Guedes de Melo; Ana Luíza Mendes Amorim Caparroz; Mirhelen Mendes de Abreu; Daniela Castelo Azevedo; Leonardo Santos Hoff; Sérgio Candido Kowalski; Themis Mizerkowski Torres; Solange Murta Barros; Gilda Aparecida Ferreira; Odirlei André Montecielo; Ricardo Machado Xavier; Virgínia Fernandes Moça Trevisani (Advances in Rheumatology, 2023)
Abstract Clinical practice guidelines (CPG) are developed to align standards of health care around the world, aiming to reduce the incidence of misconducts and enabling more effective use of health resources. Considering the complexity, cost, and time involved in formulating CPG, strategies should be used to facilitate and guide authors through each step of this process. The main objective of this document is to present a methodological guide prepared by the Epidemiology Committee of the Brazilian Society of Rheumatology for the elaboration of CPG in rheumatology. Through an extensive review of the literature, this study compiles the main practical recommendations regarding the following steps of CPG drafting: distribution of working groups, development of the research question, search, identification and selection of relevant studies, evidence synthesis and quality assessment of the body of evidence, the Delphi methodology for consensus achievement, presentation and dissemination of the recommendations, CPG quality assessment and updating. This methodological guide serves as an important tool for rheumatologists to develop reliable and high-quality CPG, standardizing clinical practices worldwide.